Revision of Alpheus euphrosyne De Man, 1897 andA. microrhynchus De Man, 1897, with description of three new species and taxonomic remarks on several other morphologically and ecologically similar snapping shrimps (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2023)
Alpheus euphrosyne De Man, 1897 and A. microrhynchus De Man, 1897, two taxonomically challenging snapping shrimps without extant original type material, are rediagnosed based on recently collected and older museum material and adhering closely to their original descriptions. Two male specimens from Java and Kalimantan are designated as neotypes for A. euphrosyne and A. microrhynchus, respectively. Alpheus tirmiziae Kazmi, 1974 is placed in the synonymy of A. euphrosyne. The distributional range of A. euphrosyne extends from the South China Sea through the Sunda Shelf to the northern Arabian Sea. Alpheus eurydactylus De Man, 1920 is removed from the synonymy of A. euphrosyne and redescribed based on De Man’s type material from Java and new material from South-East Asia, Indonesia and northern Australia. Alpheus richardsoni Yaldwyn, 1971, previously often regarded as a subspecies of A. euphrosyne, is confirmed as a valid species morphologically and ecologically distinct from A. euphrosyne. In addition, A. richardsoni is geographically separated from A. euphrosyne, being confined to subtropical and temperate waters of Australia and New Zealand. Alpheus microrhynchus appears to be geographically restricted to South-East Asia, with confirmed records from Thailand, peninsular Malaysia and Borneo, where it occurs in transitional freshwater to brackish water habitats. Alpheus cyanoteles Yeo & Ng, 1996 is currently seen as the only true freshwater snapping shrimp. This unique species is morphologically almost identical with A. microrhynchus and is presently known only from a few localities in southern Thailand, peninsular Malaysia and western Borneo (Sarawak). Three species that were previously confused with A. euphrosyne, A. euphrosyne euphrosyne or A. euphrosyne richardsoni, are described as new to science: A. nomurai sp. nov. from Japan, Korea and Taiwan; A. takla sp. nov. from South-East Asia, Philippines, Indonesia, Papua New Guinea and Australia; and A. mangalis sp. nov. from Singapore, Malaysia, Philippines, Indonesia, northern Australia, Taiwan and possibly New Caledonia. Alpheus takla sp. nov. may represent the largest presently known snapping shrimp, with the total body length reaching 90 mm and the length of the major chela reaching 52 mm; this species, locally known as takla, is consumed in some parts of the Philippines. The taxonomic identity of the material from the western and northern Indian Ocean previously reported as A. euphrosyne euphrosyne remains uncertain. Alpheus malabaricus songkla Banner & Banner, 1966 is tentatively elevated to species rank, as Alpheus songkla stat. nov. This taxon remains problematic, mainly because the original type material from Songkhla Lake, Thailand, is composed exclusively of females; its status is discussed based on the reexamination of type specimens and material tentatively identified as A. cf. songkla, which appears to have some affinities with both A. songkla and A. eurydactylus. In addition, taxonomic, biogeographic and/or ecological remarks are provided for five further species, which in the past were compared with A. euphrosyne, A. richardsoni and A. microrhynchus or are morphologically similar to them. These species are: A. paludicola Kemp, 1915 from India; A. nipa Banner & Banner, 1985 from Indonesia; A. bunburius Banner & Banner, 1982 from western Australia; A. pontederiae de Rochebrune, 1883 from both sides of the Atlantic Ocean; and A. firmus Kim & Abele, 1988 from the tropical eastern Pacific. The heterogeneity of the Panamanian and Mexican material currently assigned to A. firmus is discussed in more detail.